Value Engineering in Mutiara Gading Bekasi City Housing Project - Adi Susanto, Riki; Paryati, Ninik; Nuryati, Sri (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Value Engineering is a method or technique of cost control. This technique uses an approach by analyzing the value with its function where the process taken is to reduce cost reduction while still paying attention to its position. Housing prices have increased drastically yearly in the Mutiara Gading City housing project. Therefore, selecting construction materials is critical to efficient project planning. In the Mutiara Gading City housing project, there are several construction works, wall work, floor work, and sill and window work, one of the jobs with the highest cost so that it can do value engineering. This study aims to obtain alternative proposed materials and the best choices for wall, floor, sill, and window work. Therefore, Value Engineering is needed to eliminate unnecessary costs and effort. So that the value or price of the project can be reduced, in its application, Value Engineering consists of 4 stages, namely the information stage, the creative stage, the analysis stage, and the recommendation stage. The results showed that for wall masonry work, a savings of Rp. 369,203,509.67 or 24.31% of the initial cost was obtained for floor work, a savings of Rp. 39,304,125.00 or 8.60% of the initial cost, and obtained cost savings of Rp for work sills and windows. 22,082,604.07 or 6.51% of the initial cost. Of all the selected work items, a total savings of Rp. 430,590,238.74 or 7.01% of Rp. 6,139,876,202.60 total project cost, which includes 35 housing units.